Contribution to the study of the wolverine (Gulo gulo, Linné 1758) - Thibert, Hélène (CCSD, 2012)
The wolverine is an animal not well known by the general public, who carry on a reputation of ferocity, voracity and aggressiveness more intense than any other predator, even he is small sized. Known as “The North Devil”, this small carnivore is the bigger representative of the family of the mustelids. He can be found in North America and in the north of Eurasia, inside severe climates where he is the subject of several research programs and conservation plans. This work aims to resume biology and ecology of the wolverine, current research projects and conservation strategies currently displayed; and finally to explore briefly his relationships with humans. Le glouton est un animal méconnu du grand public, qui supporte une réputation de férocité, d’agressivité et de voracité plus importante que n’importe quel autre prédateur, malgré sa petite taille. Perçu comme le « démon du Nord », ce petit carnivore est le plus grand représentant de la famille des mustélidés. On le retrouve en Amérique du Nord et au Nord de l’Eurasie, au sein de climats rigoureux où il fait actuellement l’objet d’études et de plans de conservation. Ce travail se propose de résumer les caractéristiques biologiques et écologiques du glouton, les projets de recherche en cours et les stratégies de conservation actuellement déployées et enfin d’explorer brièvement ses relations avec l’espèce humaine.